Managing Respiratory Emergencies: A Qualitative Exploration of Teamwork and Communication Between Respiratory Therapists and Nurses in Critical Care Settings - Hamad Saleh Khalef Alanazi, Faisal Saad Ali Alanazi, Ali Abdulaziz Ali Alsubaihi, Abdulaziz Tomayhere Musaied Aljameeli, Sattam Dinar Labidan Alanazi, Saleh Owaid Ghadban Alanazi, Abdullah Maayouf Khalif Alanezi, Mamdoh Farhan Monazel Alanazi, (Journal of International Crisis and Risk Communication Research, 2024)
Effective teamwork and communication between respiratory therapists and nurses are crucial for managing respiratory emergencies in critical care settings. This qualitative study explores the perspectives and experiences of respiratory therapists and nurses regarding their collaboration in managing respiratory emergencies in intensive care units (ICUs) in Saudi Arabia. Through semi-structured interviews, the study investigates the factors that facilitate or hinder effective teamwork and communication, as well as the strategies employed to overcome challenges. The findings reveal that clear role delineation, mutual respect, and effective communication channels are key enablers of successful collaboration. However, participants also identify barriers such as workload pressures, lack of standardized protocols, and hierarchical structures that can impede timely and efficient emergency response. The study highlights the importance of interprofessional education, simulation training, and the development of standardized communication tools to enhance teamwork and patient outcomes in critical care settings. The insights gained from this study can inform interventions and policies aimed at optimizing the management of respiratory emergencies through improved collaboration between respiratory therapists and nurses.